IFPRI key facts series: Food and nutrition security - Banda, Chimwemwe (International Food Policy Research Institute, 2022)
This is a second Food and Nutrition Key Facts sheet in a series of Key Facts sheets that IFPRI is producing based on Integrated Household Surveys (IHS). The purpose of the series is to present data relevant to key policy issues on agriculture, food systems, and development topics in Malawi. Other Key Facts Sheets are available on our website at massp.ifpri.info.